Bacteriophages against methicillin resistant Staphylococcus aureus strains - V.A. Poniatovskyi; O.L. Bondarchuk; M.O. Prystupiuk; O.O. Smikodub; V.P. Shyrobokov (Medičnì Perspektivi)
Staphylococcus aureus is one of the most common opportunistic pathogens that causes a variety of diseases, from minor skin infections to life-threatening sepsis, meningitis, pneumonia and a number of other diseases. Particular attention was paid to methicillin-resistant Staphylococcus aureus (MRSA) strains with multiple drug resistance. The purpose of this study is investigation of the sensitivity of clinical isolates of Staphylococcus aureus, including methicillin-resistant strains, to bacteriophage drugs and determination of possibility of using this agent for the treatment of staphylococcal infections. A number of classical and modern microbiological methods for the isolation and identification of Staphylococcus aureus: an indication of genes, responsible for antibiotic resistance (PCR analysis), determination of sensitivity to antibiotics (disc diffusion method) and bacteriophages (spot test, Gracia method, Appelman method) were used in the study. The susceptibility analysis of Staphylococcus aureus with presence and absence of mecA gene to the commercial bacteriophage product – “PYOFAG® BACTERIOPHAGE POLYVALENT” was performed. The results of the study showed that the total number of susceptible strains of bacteria was 95±0,2%. The use of investigational Bacteriophage drug for the treatment of furunculosis caused by MRSA has shown positive results. After one week of using the bacteriophage as monotherapy, the patient experienced regression of the clinical symptoms. For the period of use no adverse effects have been detected. Thus, the phage drugs using can become an important tool in the control of antibiotic-resistant strains, which cause a variety of infections in humans.